Fatty acid and phytosterol accumulation during seed development in three oilseed species. (26th May 2016) - Roche, Jane; Mouloungui, Zephirin; Cerny, Muriel; Merah, Othmane
Summary: This study was carried out to compare the kinetic accumulation of bioactive lipids during seed development in three oil crops rapeseed, sunflower and woad. Field experiments were conducted under organic conditions during 3 years. After flowering, seeds were collected each 4–5 days until harvest. The three species differed by the quantity and quality of both fatty acids and sterols. Higher levels of phytosterols and fatty acids were reached between 20 and 40 days after flowering (DAF) in sunflower, 40 and 60 DAF in rapeseed and 25 and 45 DAF for woad. The modification of lipid composition during the grain filling depends on species. Knowledge of the composition and accumulation of fatty acids and phytosterols in sunflower, rapeseed and woad seeds would assist in efforts to achieve industrial applications. These seeds may give an interesting source of bioactive lipids. Abstract : Total phytosterol contents of sunflower, rapeseed and woad seeds during seed ripening. SDM: seed dry matter; DAF: days after flowering.